Aspectos fitossociológicos da comunidade de plantas daninhas na cultura do feijão sob diferentes sistemas de preparo do solo - Silva, A.A.; Silva, C.S.W.; Souza, C.M.; Souza, B.A.; Fagundes, J.L.; Falleiro, R.M.; Sediyama, C.S. (Planta Daninha, 2005)
Avaliou-se, neste trabalho, os efeitos de sistemas de preparo do solo: [(plantio direto (PD), arado de discos (AD), arado de aivecas (AA), grade aradora (GA), grade aradora+arado de discos (GA+AD) e grade aradora+arado de aivecas (GA+AA)] sobre a comunidade de plantas daninhas da cultura do feijão. Este experimento foi desenvolvido em área onde os diferentes sistemas de preparo do solo estavam sendo avaliados desde 1985. Todavia, os resultados aqui apresentados são referentes apenas à safra 2000/2001. Neste ensaio, as parcelas foram subdivididas pela aplicação ou não de herbicidas em pós-emergência. As plantas daninhas presentes na área experimental foram separadas por espécie, classificadas, secadas e pesadas, sendo analisadas segundo a sua importância relativa dentro da comunidade, através dos índices fitossociológicos de densidade, freqüência e dominância. A aplicação de herbicidas em pós-emergência diminuiu a biomassa total das plantas daninhas, e esse efeito foi independente do sistema de preparo. Os sistemas de preparo do solo e a aplicação de herbicida em pós-emergência alteraram a importância relativa das plantas daninhas dentro da comunidade. As espécies que apresentaram maior importância foram Cyperus rotundus, nos tratamentos com preparo convencional do solo, e Galinsoga parviflora, no plantio direto.

Tillage systems change the floral composition of a weed community. The changes can be either a simple fluctuation in plant population or the establishment of a permanent new weed community, affecting competition, management and control. The aim of this work was to evaluate the effects of tillage systems on the weed community in bean crop in areas where different tillage systems were being applied since 1985.The experimental soil was cultivated with annual cultures and submitted to six tillage systems: no-tillage (PD), moilboard plow (AD), plow of disc (AA), heavy bars (GA), heavy bars + moilboard plow (GA+AD) and heavy bars + plow of disc (GA+AA). The results discussed in this work are related to the 2001 winter-spring crop season only. The plots were divided in two sub-plots, and submitted or not to treatment with post-emergence herbicide, resulting in a complete randomized block design with four replications. The weeds were grouped by species, classified, dried and weighed. Total dry biomass and density of the weeds were submitted to the Tukey test. The weed species were analyzed according to their relative importance in the weed community, taking into account the phytosociological indices of density, frequency and dominance. Herbicide application in post-emergence reduced the total biomass of the weeds. Herbicide effect was independent of the soil tillage systems used. The soil tillage systems and herbicide application in post-emergence modified the relative importance of the weed species in the community. The species showing higher relative importance were Cyperus rotundus, in the treatments under conventional soil preparation, and Galinsoga parviflora, under no-tillage, mainly where the herbicide was applied in post-emergence.
Keywords: Plantio direto; Plantio convencional; Importância relativa; Índices fitossociológicos